Using Tomato Recombinant Lines to Improve Plant Tolerance to Stress Combination Through a More Efficient Nitrogen Metabolism - Lopez-Delacalle, María; Camejo, Daymi M.; García-Martí, María; Nortes, Pedro A.; Nieves-Cordones, Manuel; Martínez, Vicente; Rubio, Francisco; Mittler, Ron; Rivero, Rosa M. (Frontiers in Plant Science, 2020)
The development of plant varieties with a better nitrogen use efficiency (NUE) is a means for modern agriculture to decrease environmental pollution due to an excess of nitrate and to maintain a sufficient net income. However, the optimum environmental conditions for agriculture will tend to be more adverse in the coming years, with increases in temperatures, water scarcity and salinity being the most important productivity constrains for plants. NUE is inherently a complex trait, as each step, including N uptake, translocation, assimilation, and remobilization, is governed by multiple interacting genetic and environmental factors. In this study, 2 recombinant inbred lines (RIL-66 and RIL-76) from a cross between S. lycopersicum and S. pimpinellifoilum with different degree of tolerance to the combination of salinity and heat were subjected to a physiological, ionomic, metabolomic amino acid profile and transcriptomic gene expression study to better understand how nitrogen metabolism is affected in tolerant plants as compared to sensitive ones. The ionomics results showed a different profile between the 2 RILs, with K+ and Mg2+ being significantly lower in RIL-66 (low tolerant) as compared to RIL-76 (high tolerant) under salinity and heat combination. No differences were shown between the two RILs in N total content; however, N-NO3- was significantly higher in RIL-66, whereas N-Norg was lower as compared to the other genotype, which could be correlated with its tolerance to the combination of salinity and heat. Total proteins and total amino acid concentration were significantly higher in RIL-76 as compared to the sensitive recombinant line under these conditions. Glutamate, but more importantly glutamine, was also highly synthesized and accumulated in RIL-76 under the combination of salinity and heat, which was in agreement with the upregulation of the nitrogen metabolism related transcripts studied (SlNR, SlNiR, SlGDH, SlGLT1, SlNRT1.2, SlAMT1 and SlAMT2). This study emphasized the importance of studying abiotic stress in combination and how recombinant material with different degrees of tolerance can be highly important for the improvement of nitrogen use efficiency in horticultural plants through the targeting of N-related markers.